Social Media and Firm Performance: Empirical Study on Listed Indonesian Firms - Shafa, Almadea; Puspitasari, Evita (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine whether the use of Twitter and Instagram by companies has an impact on their operational and financial performance. Operational performance is evaluated using Return on Assets (ROA) and net income. For financial dissemination activities, social media usage is measured by the number of tweets and posts related to finance, while financial performance is measured using Tobin’s Q and average daily market returns. Tobin’s Q is a financial metric that is often used to assess a company’s investment attractiveness and efficiency in utilizing its assets. This study uses a quantitative method using multiple regression analysis. The sample consists of 86 companies listed on the Kompas100 index from August 2023 to January 2024. The results of the study indicate that the use of Twitter and Instagram simultaneously has a significant effect on net income and Tobin’s Q, but not on ROA and average daily market returns. In addition, none of the Twitter and Instagram usage variables are significantly related to the company’s operational and financial performance. The findings of this study can benefit companies by encouraging the to reassess their social media strategies in order to better achieve their goals, both operational and financial goals.